一种基于RIS辅助D2D保密通信的资源分配方法及装置 (2023)
本发明提供了一种基于RIS辅助D2D保密通信的资源分配方法及装置，包括：采用RIS辅助D2D通信，保证基站发射功率约束、D2D传输速率约束、RIS相移约束，得到CU最大保密传输速率模型；对发射波束和RIS联合设计，得到线性分式规划约束模型；构建并行CNN模型，通过对其训练，得到最佳模型，进而求得最大保密传输速率。本发明提出基于一种并行CNN的资源分配算法，相对于传统的无RIS保密传输方案和采用人工噪声方案，在保证D2D用户正常通信前提下显著提高了CU的保密速率。 The invention provides a resource allocation method and device based on RIS-assisted D2D secret communication, and the method comprises the steps: employing RIS-assisted D2D communication, guaranteeing base station transmitting power constraint, D2D transmission rate constraint and RIS phase shift constraint, and obtaining a CU maximum secret transmission rate model; performing joint designing on the transmitted beam and the RIS to obtain a linear fraction planning constraint model; and constructing a parallel CNN model, and training the parallel CNN model to obtain an optimal model so as to obtain the maximum confidential transmission rate. According to the resource allocation algorithm based on the parallel CNN, compared with a traditional RIS-free confidential transmission sch